Strategi Kepala Taman Pendidikan Al-Qur’an (TPQ) dalam Meningkatkan Mutu Pendidikan Al-Qur’an - Aryel, Raul; Iklhas, Al (Lembaga Yasin AlSys, 2024)
TPQ Jannatul Mukmin Mosque is one of the Qur'anic educational institutions located in Kubu Dalam Parak Karakah Village, East Padang District which was established in 1984. The purpose of this study is to describe how the planning, implementation, and eval_uation of the strategy of the head of TPQ in improving the quality of Qur'an education at the TPQ Jannatul Mukmin Mosque Kubu Dalam Parak Karakah East Padang. The research method used in this study is qualitative with the type of case study research. In this study, structured interviews were conducted with the research subjects, namely the principal, the teacher of Qur'an Education and the homeroom teacher of grade IV TPQ of the Jannatul Mukmin Mosque of Kubu Dalam Parak Karakah East Padang. The collection techniques used are interviews, observations, and documentation. The findings were analyzed using the Miles and Huberman Model data analysis, and the validity of the data was tested using data triangulation. The results of the study show that the strategy of the head of TPQ in improving the quality of Qur'an education at the TPQ of the Jannatul Mukmin Mosque in the Karakah Parak Padang Timur through several stages, namely; 1) Strategic planning of the head of TPQ includes; annual, semester, monthly, weekly and daily program plans in accordance with the vision and mission of TPQ Jannatul Mukmin Mosque; 2) The implementation of the strategy of the head of TPQ has carried out TPQ activities through mobilization, encouragement and guidance to all human resources and personnel in TPQ, properly and directed in accordance with the TPQ program both annual, semester, monthly, weekly, and daily, which is based on the standardization of religious education; 3) eval_uation of the strategy of the head of TPQ in several stages, namely; The eval_uation carried out at the beginning is a tool to anticipate the existence of obstacles and obstacles as well as deviations from the standards and objectives that have been prepared. All eval_uations have been carried out by the head of TPQ as appropriate. Therefore, the strategy implemented by the Head of the TPQ of the Jannatul Mukmin Mosque can be used by other TPQ heads in improving the quality of Qur'an education in TPQ while still paying attention to the characteristics of each TPQ.